Women in the story of Jesus: the gospels through the eyes of nineteenth-century female biblical interpreters - Weir, Heather E.; Taylor, Marion Ann (William B. Eerdmans Publishing Company, 2016)
Part 1. Heart and hands: women's spirituality -- 1. Mary: the exemplary disciple -- Clara Lucas Balfour: humility: the noblest virtue -- Elizabeth Stuart Phelps: receiving the divine -- Sarah Trimmer: blessed humility -- Gracilla Boddington: worshipping with Mary -- Mary Anne SchimmelPennick: hail her as the woman -- Elizabeth Wordsworth: Cleopatra or Mary? -- Christina Georgina Rossetti: the veiled virgin -- Elizabeth Rundle Charles: communion and sacrifice -- 2. Mary and Martha of Bethany: spirituality in the workplace -- Esther Hewlett Copley: consecrated abilities -- Clara Lucas Balfour: action and contemplation -- Nina L. McFadyen: the happy home in Bethany -- Etty Woosnam: meddlesome Matty -- M. G.: work and devotion -- Mary Ann Smith: doing what we can -- Part 2. Unsealed lips: women preaching -- 3. Anna: the vocation of a woman preacher -- Sarah Hale: Anna's spiritual superiority -- Elizabeth Baxter: a role model for female ministry -- Elizabeth Wilson: a woman with a vocation -- M. G.: A widow's vocation: a sermon -- 4. The woman at the well: the first Samaritan evangelist -- Clara Lucas Balfour: a changed woman -- Elizabeth Baxter: the gospel preacher -- Phoebe Palmer: women's preaching justified -- Hannah Jane Locker-Lampson: empathetic evangelistic preaching: a sermon -- Mary Elizabeth Beck: bearing the words of life: a sermon -- 5. Herodias and Salome: the royal tigresses judged -- Harriet Beecher Stowe: it's all about power -- Euphemia Johnson Richmond: voluptuous dancing -- Mrs. Donaldson: the great danger of worldly amusements: a sermon -- Margaret Black: pleasing the tyrant -- Part 3. Unveiled eyes: women and the biblical text -- 6. A woman of Canaan: experiencing the text -- Caroline Pridham: Gentile dogs? -- Elizabeth Rundle Charles: traveling to Tyre -- Mrs. Donaldson: dealing with our demons: a sermon -- 7. The adulterous woman: teaching troublesome texts -- Lucy Barton: heart searching -- Mary Cornwallis: we behold the woman -- Charlotte Bickersteth Wheeler: who cound invent it? -- Elizabeth Baxter: where is the man? -- Josephine Butler: the sex bias of the commentators -- 8. Mary Magdalene: receiving the text -- Anna Jameson: mythic Magdalene -- Harriet Beecher Stowe: redeemed penitent -- Charlotte Bickersteth Wheeler: carry the glad tidings -- Elizabeth Baxter: apostle of the resurrection -- Elizabeth Cady Stanton: gullible woman -- Amelia Gillespie Smyth: harmonizing Magdalene -- Elizabeth Rundle Charles: hidden depths